Perception of a group of teenagers of their parents' educational styles (Journal of Parents and Teachers, 2014)
The interpersonal relationship between parents and children requires a series of adjustments and balances; it also requires a dialogue framed in the separation of equal tasks for each of the members. Several parental educational styles stand out: protectionist, unconcerned, authoritarian, permissive and dialogic (the one recommended by the authors). Above all, it should be remembered that the school cannot replace the work of parents; it should also be remembered that an adolescent needs points of reference to look to in order to grow and to exercise constructive criticism. At the end of the article there is a questionnaire to assess the perception that adolescents have of their parents' educational styles; the questionnaire is accompanied by some data for reflection.
Keywords: education; parents; teenagers; educational styles; survey